Prevalence of Musculoskeletal Disorders Associated with 3 Types of Work in Indonesia - Zaimah Maznah, Fina (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
In Indonesia research related to Musculoskeletal Disorders (MSDs) is still in the developing phase. MSDs have been analyzed as a major cause of errors, accidents and absences of workers in many countries and industries. This study investigated the prevalence of MSDs and the relationships between office workers, garbage collectors, and farmers. A direct survey was completed in December 2023. A total of 60 questionnaires were fully filled in and used for data analysis. These three occupational groups were chosen as a comparison of MSD risk in formal and informal work in developing countries mainly in Indonesia. The purpose of this study is to determine the prevalence of musculoskeletal disorders in each work group so that it is expected to provide an understanding of the magnitude of the problems associated with MSD and can also be used as a basis for carrying out more effective ergonomic interventions. A questionnaire of the Standardized Nordic Questionnaire (SNQ) was used in this study. The prevalence of MSDs in the three occupational groups with an average high score was in the neck, shoulders, lower back and knees. The highest prevalence of MSDs for each type of work is for office workers is the neck area (70%), for garbage transport is the shoulder area (85%), and for farmers is the lower back area (70%). Length of work and duration of work per day are variables that have a significant relationship with MSD complaints that were felt during the last 12 months in all three work groups. Although no statistical testing was conducted, the second group consisting of garbage transporters tended to have a higher prevalence compared to the other groups.